A Rationalization of the Precautionary Demand for Cash - Whalen, Edward L. (Quarterly Journal of Economics, 1966)
Introduction, 314. — Definition of the precautionary demand for cash, 314. — The concepts, 315. — Optimal precautionary cash balances, 316. — Comparison with transactions demand for cash, 320. — Comparison with related studies, 320. — Appendix, 322.